DISCOURSES OF PERSONALITY’S SELF-REALIZATION IN THE INTERNET - Іщук, С. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article deals with the basic intentions of personality’s self-realization in the Internet. By means of segmentation of the Internet communication space the domination of the discourses of advertising, pedagogy, politics and game playing is grounded. Within the frames of these discourses the two basic intentions of personality’s self-realization in the Internet are observed: the readiness to think and to consume.